The hybrid anterior cruciate ligament reconstruction surgical technique does permit an accelerated early functional recovery and return to sport. - Annear, Peter (Orthop J Sports Med, 2017)
OBJECTIVES: A major reason for undergoing anterior cruciate ligament reconstruction (ACLR) for patients is to return to high demand activity and sport. Published literature supports a return to sport (RTS) at 6-12 months, though the recovery of lower limb strength and functional symmetry is critical and is linked with a patient’s ability to RTS, as well as reducing the incidence of secondary re-tear. This study aimed to compare clinical outcomes and RTS between patients undergoing ACLR utilizing a hamstring graft and those undergoing a hybrid technique which augments the hamstring graft with a synthetic LARS ligament. METHODS: A non-randomized study design was used to compare clinical outcomes at 10-12 months post-surgery, in 82 patients undergoing conventional ACLR via a hamstring graft (HG) and 35 patients undergoing a hybrid hamstring/LARS graft (HLG). All patients were assessed using a range of patient-reported outcome (PRO) scores (IKDC, KOOS, Cinncinati, Lysholm, SF-36, Tegner, Noyes, Global Rating of Change – GRC). Limb symmetry indices (LSIs) presenting the operated limb as a percentage of the unaffected limb were calculated for several strength/functional assessments (peak isokinetic quadriceps and hamstring strength, the single, triple and triple crossover hop for distance, and the 6 m timed hop). RESULTS: There were no group differences (p>0.05) in patient demographics and the majority of PROs. The HLG group perceived themselves to be significantly ‘more recovered’ (p=0.046) on the GRC scale (HLG = 3.2, HG = 2.2), and also reported a significantly greater (p=0.004) Tegner score (HLG = 7.2, HG = 5.9). For the HG group, 62% of patients had returned to Noyes Level 1 or 2 activities, versus 80% of the HLG group. For the Tegner score, 57% of patients reported a score >6, versus 77% of the HLG group. There were no significant differences (p>0.05) in LSIs between groups for the strength and functional hop tests. However, the HLG group demonstrated a mean LSI above 90% for all four hop tests, while all four were below 90% in the HG group. Both groups demonstrated mean hamstring strength LSIs above 90%, while the quadriceps strength LSI was 81.9% and 85.8% for the HG and HLG groups, respectively. CONCLUSION: Patients in the HLG group perceived themselves to be more recovered, and had returned to a higher level of activity/sport, compared with the HG group. While not significant, the HLG group did demonstrate more favorable functional hop and quadriceps strength LSIs, which has been linked with the ability to RTS and the incidence of ACL re-tear. A larger patient cohort and follow-up is required to observe long-term outcomes.